From the Roman Empire to Rio de Janeiro: society and models of sustainable water management - Prioste, Mauro; Formiga-Johnsson, Rosa Maria; Ohnuma Junior, Alfredo Akira (Sustainability in Debate, 2021)
The purpose of this article is to carry out a content analysis around the historical influence of ancient societies’ ideas regarding sustainable water management. Ancient civilizations developed models and practices for the drainage, intake and transport of rainwater and wastewater. Despite the Roman Empire and the Moorish domination, Lisbon maintained its characteristics until the formation of the Kingdom of Portugal, undergoing an urban and sanitary revolution, which lasted until the 19th Century, when the Portuguese Royal Family moved to Brazil. Rio de Janeiro was chosen as the capital of the Kingdom of Portugal, undergoing several alterations inherited from the models and practices of irrigation techniques, hydraulic engineering and architecture of Lisbon. Data compilation in electronic spreadsheets and the use of NVivo software facilitated organizing the information and conclude that sustainable management models can be replicated as an inheritance of ancient societies.